Δ-Tocotrienol Oxazine Derivative Antagonizes Mammary Tumor Cell Compensatory Response to CoCl2-Induced Hypoxia. (22nd July 2014) - Ananthula, Suryatheja; Parajuli, Parash; Behery, Fathy A.; Alayoubi, Alaadin Y.; Nazzal, Sami; El Sayed, Khalid; Sylvester, Paul W.
Abstract : In response to low oxygen supply, cancer cells elevate production of HIF-1 α, a hypoxia-inducible transcription factor that subsequently acts to stimulate blood vessel formation and promote survival. Studies were conducted to determine the role of δ -tocotrienol and a semisynthetic δ -tocotrienol oxazine derivative, compound 44, on +SA mammary tumor cell hypoxic response. Treatment with 150 µ M CoCl2 induced a hypoxic response in +SA mammary tumor cells as evidenced by a large increase in HIF-1 α levels, and combined treatment with compound 44 attenuated this response. CoCl2 -induced hypoxia was also associated with a large increase in Akt/mTOR signaling, activation of downstream targets p70S6K and eIF-4E1, and a significant increase in VEGF production, and combined treatment with compound 44 blocked this response. Additional in vivo studies showed that intralesional treatment with compound 44 in BALB/c mice bearing +SA mammary tumors significantly decreased the levels of HIF-1 α, and this effect was associated with a corresponding decrease in Akt/mTOR signaling and activation of downstream targets p70S6kinase and eIF-4E1. These findings demonstrate that treatment with the δ -tocotrienol oxazine derivative, compound 44, significantly attenuates +SA mammary tumor cell compensatory responses to hypoxia and suggests that this compound may provide benefit in the treatment of rapidly growing solid breast tumors.